2013
DOI: 10.5713/ajas.2013.13184
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Novel Denitrifying Bacterium <italic>Geobacillus</italic> sp. SG-01 Strain from Wood Chips Composted with Swine Manure

Abstract: Nitrate contamination in ground and surface water is an increasingly serious environmental problem and only a few bacterial strains have been identified that have the ability to remove nitrogen pollutants from wastewater under thermophilic conditions. We therefore isolated thermophilic facultative bacterial strains from wood chips that had been composted with swine manure under aerated high temperature conditions so as to identify strains with denitrifying ability. Nine different colonies were screened and 3 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Examination of carbohydrate degrading activity of the isolate demonstrated that the isolate could be considered as possible source of biotechnologically valuable enzymes such as cellulases, amylase and xylanase. G. thermodenitrificans SG-01, SG-02 and SG-03 gave positive result for utilization of fructose, fructose and sucrose and sucrose, respectively (Yang et al 2013).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Examination of carbohydrate degrading activity of the isolate demonstrated that the isolate could be considered as possible source of biotechnologically valuable enzymes such as cellulases, amylase and xylanase. G. thermodenitrificans SG-01, SG-02 and SG-03 gave positive result for utilization of fructose, fructose and sucrose and sucrose, respectively (Yang et al 2013).…”
Section: Resultsmentioning
confidence: 97%
“…Geobacillus sp. SG 01 presented growth at NaCl concentration (0-2%) with optimal growth at 1% NaCl (Yang et al 2013). Geobacillus pallidus p26 grew within the NaCl range of 2-5% (Celik et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most denitrifying bacteria are suitable for growth in neutral and weak alkali environments (Zhang et al 2012; Ye et al 2016). The optimum pH of denitrification by most denitrifying bacteria was 7–8 (Tang et al 2014; He, Li, and Xu 2015; Yang et al 2013). However, when the pH was out of the optimal range, the denitrification capacity can be decreased.…”
Section: Discussionmentioning
confidence: 99%
“…They are usually sensitive to oxygen, and the expression of enzymes related to the denitrification process might be suppressed under aerobic conditions (Zheng et al, 2012; Zhou et al, 2014; Zhao et al, 2018). Aerobic denitrifying bacterium is able to utilize oxygen and nitrate or nitrite as electron acceptors simultaneously under aerobic condition (Yang et al, 2013; Huang et al, 2015; Zhao et al, 2018). Thus, compared to conventional denitrifying bacterium, aerobic denitrifying bacterium might be more suitable for nitrite pollution elimination in scenarios including intensive aquaculture industry where adequate dissolved oxygen was needed for aquatic animals (Li et al, 2008).…”
Section: Introductionmentioning
confidence: 99%